Chemical Profile and Alcoholic Fermentation Analysis of the Ethiopian Wild Edible Fruit Physalis peruviana L. - Tesfom Zeru Zereahannes; Tarekegn Berhanu Esho; Alayu Woldtensay Teklie; Henock Woldemichael Woldemariam; Neela Satheesh; Aselefech Sorsa Wotango (Applied Sciences)
Physalis peruviana Linnaeus, also called Cape gooseberry, has been used extensively as a medicinal herb since ancient times. The current study is the very first investigation into the nutrient characteristics of Physalis peruviana L. fruits found in Ethiopia. Its main objective is to investigate the nutritional, antinutritional, and antioxidant capacity of the edible fruit of Physalis peruviana L. Three different drying conditions (shade, sun, and oven drying) were investigated to observe their effects on the chemical composition of the fruit. The antioxidant activities were quantified using DPPH (2,2-diphenylpicrylhydrazyl) and FRAP (ferric reducing antioxidant power) assays. Total flavonoid and total phenol contents were also determined for all dried samples. The shade-dried sample exhibited a better composition with regard to most of the characterized constituents than the other dried samples. From all of the results obtained, the shade-dried sample showed higher antioxidant activity, and, among the investigated minerals, its K content was found to be the highest (313.66 ± 0.05 g/100 g). However, the Fe content (in the oven-dried sample) was found to be the lowest (0.06 ± 0.10 g/100 g) of the investigated minerals. Through fermentation using Saccharomyces cerevisiae, the alcoholic content of the fruit was 9.11%, 9.90%, and 12.34% after 24, 48, and 72 h of fermentation time, respectively. It was also observed that the high temperature used in the drying process led to content loss in the fruit samples. This was evident in the oven-dried samples. It is expected that the analysis of the effects of drying on fruit composition can contribute to a better understanding of fruit storage/preparation and provide useful information on fruit product formulations.